Demand for and intensity of use of extension services among cocoa farmers in Ghana: the heckpoisson approach. - Enoch Kwame Tham-Agyekum; Fred Ankuyi; Prince Asiedu; Akua Yeboah Oduro-Owusu; Ernest Laryea Okorley; Stephen Prah; John-Eudes Andivi Bakang; Prince Amoako (CV. AFDIFAL MAJU BERKAH, 2023)
In response to the evolving landscape of agricultural extension services, a paradigm shift is imperative, moving away from the traditional supply-centric approach to one that recognizes farmers as active participants influenced by socio-economic factors. This transformation is especially pertinent for cocoa farmers, whose livelihoods hinge on this crop. To elucidate this shift, our study employs a multistage sampling technique to select 400 cocoa farmers in the Tafo District, Eastern Region, Ghana to ensure representativeness and diversity. The Heckpoisson model analysis reveals that farmers' demand for and intensity of use of extension services are intricately linked to a spectrum of socio-economic factors; farming experience, cooperative membership, farm size, sex, number of farms, religion, land tenure, marital status, household size, access to credit, distance to the farm, age, and years of formal education. Building upon our insights, we recommend that extension service providers tailor their services to align with the socio-economic characteristics of farmers